Regulatory constraints on bank leverage: Issues and lessons from the Canadian experience - Etienne Bordeleau; Allan Crawford; Christopher Graham (Bank of Canada, 2009)
The Basel capital framework plays an important role in risk management by linking a bank's minimum capital requirements to the riskiness of its assets. Nevertheless, the risk estimates underlying these calculations may be imperfect, and it appears that a cyclical bias in measures of risk-adjusted capital contributed to procyclical increases in global leverage prior to the recent financial crisis. As such, international policy discussions are considering an unweighted leverage ratio as a supplement to existing risk-weighted capital requirements. Canadian banks offer a useful case study in this respect, having been subject to a regulatory ceiling on an unweighted leverage ratio since the early 1980s. The authors review lessons from the Canadian experience with leverage constraints, and provide some empirical analysis on how such constraints affect banks' leverage management. In contrast to a number of countries without regulatory constraints, leverage at major Canadian banks was relatively stable leading up to the crisis, reducing pressure for deleveraging during the economic downturn. Empirical results suggest that major Canadian banks follow different strategies for managing their leverage. Some banks tend to raise their precautionary buffer quickly, through sharp reductions in asset growth and faster capital growth, when a shock pushes leverage too close to its authorized limit. For other banks, shocks have more persistent effects on leverage, possibly because these banks tend to have higher buffers on average. Overall, the authors' results suggest that a leverage ceiling would be a useful tool to complement risk-weighted measures and mitigate procyclical tendencies in the financial system.
Keywords: G01; G28; G21; 330; Financial institutions; Financial stability; Financial system regulation and policies; Finanzmarkt; Bankgeschäft; Risiko; Einlagensicherung; Bankenaufsicht; Basler Akkord; Kanada